DIGITAL HR: A REVOLUTION IN HUMAN RESOURCES MANAGEMENT IN THE DIGITAL AGE (Regional aspects of productive forces development of Ukraine, 2024)
ABSTRACTIntroduction. The revolution in human resource management in the digital era is undoubtedlydriven by key factors that represent a significant change in the approach to human resource managementin the modern world. Continuous technological development and digitalization of business areincreasingly creating the need for more efficient, flexible and innovative HR practices. The currentchallenges of globalization, the transition from an industrial economy to a networked digital economy,new speeds, mobility and transparency of business require a rethinking of the business paradigm. Theongoing digital revolution requires the transformation of traditional companies into technologycompanies. Business rules are changing to ensure success in the fast-paced digital age. However, there isstill a lack of in-depth research on the integration of digital technologies into HR processes and thedefinition of the main components of digital HR. Therefore, the questions selected for analysis areextremely important.Goal. To achieve this goal, a set of general scientific methods of cognition was applied, whichensured the consistency and logical consistency of the conclusions drawn.Methods. To achieve this goal, a set of general scientific methods of cognition, includinginstrumental, institutional, graphic, were used.Results. It has been established that digital technologies in HR help automate routine tasks,reduce errors, and increase the efficiency and convenience of processes for employees and HRprofessionals. They can collect more data, make processes transparent, fast, and objective, which is thebasis for making more informed and strategic decisions. As a result, the organization maintains itscompetitive of HR management and employee engagement.Conclusions. The findings allow us to optimize traditional processes and create new opportunitiesfor integrating strategic HR management with the company's overall business strategy, in particular,defining digital technologies in the context of the organization's culture, which may be an area for furtherresearch.Key words: digitalization, digital technologies, HR revolution, HR processes, Digital HRcomponents, HR functions.